SEPARATION OF NICKEL FROM COBALT AND MANGANESE IN THE PREGNANT LEACH SOLUTION OBTAINED FROM RE-LEACHING OF MIXED HYDROXIDE PRECIPITATE VIA SELECTIVE OXIDATIVE-PRECIPITATION USING OZON AS OXIDANT INJECTED BY SWIRLING METHOD - Tiara Sekar Kirani, Putri
Mixed Hydroxide Precipitate (MHP) is one of types of the intermediate products from the extraction process of laterite nickel ore through the hydrometallurgical route. MHP typically contains about 35-40% nickel, 2% cobalt and certain amounts of impurities such as iron, manganese and magnesium. One of the MHP purification options is the oxidation-precipitation method. The principle of separation of nickel from manganese, cobalt and iron is based on the difference in their oxidation rate to high valence cations with lower solubility. Ozone is a strong oxidizing agent with a standard potential of +2.07 V which can be generated from oxygen gas or air. This study aims to study the selective oxidation-precipitation behavior of Co, Mn and Ni in the pregnant solution of MHP re-leach using micro-nano bubbled ozone injected with a swirling technique for the separation of Ni from Co and Mn. Preparation of MHP sample from PT Trinitan Metals and Materials Tbk was carried out through a process of drying to eliminate its moisture. Characterization of MHP was carried out by moisture analysis, X-Ray Diffraction (XRD), and Atomic Absorption Spectroscopy (AAS). Afterward, the MHP leaching process was carried out with conditions referring to the previous investigation. The oxidation-precipitation experiment was designed according to the L9 (34) orthogonal array experimental design rules of the Taguchi Method. Series of experiments were carried out by varying the precipitation time (30, 60, 90 minutes), pH (3, 4, 5), ozonation time (10, 20, 30 minutes), and the flow rate of O2 gas as an ozone source (0.3, 0.5; 0.8 L/min). The results of the precipitation percentages of Ni, Co and Mn were processed using the Taguchi method and ANOVA to determine the optimum conditions and the significance of the effect of each variable on the precipitation percentages of Ni, Co, and Mn. Based on these results, further experiment was conducted to validate the effect of the variables on Ni, Co and Mn precipitation. The optimum conditions for achieving the lowest nickel co-precipitation percentage were obtained at 90 minutes precipitation period, 20 minutes ozonation period, pH 5, and 0,5 L/minute of O2 injection rate. The percentages of Co and Mn precipitation were 99.3% and 100%, respectively, with only 1.6% Ni co-precipitation. The concentrations of Ni, Co and Mn in the final solution were 40.96 g/L, 0.0076 g/L, and <0.000002 g/L with a Ni/Co ratio of 5410, respectively. The contribution effect of ozonation time, pH, and O2 flow rate on percent nickel precipitation were 22.6%, 25.2%, 18.53%, and 16.42%, respectively. The results of the validation of the effect of precipitation time, ozonation time, and pH showed the profile of nickel, cobalt, and manganese precipitation percentages which were the similar with the results of the experiments designed the Taguchi Method.